Effects of Ashwagandha (Withania somnifera) Root Extract Against Gentamicin Induced Changes of Serum Electrolytes in Rats - Shimmi, Sadia Choudhury; Jahan, Nasim; Sultana, Nayma (Journal of Bangladesh Society of Physiologist, 2012)
Background: Regulation of electrolytes and body fluids are essential for maintaining the body homeostasis. Kidney plays an important role for these regulations. Higher doses of drugs, toxins, infectious agents, chemicals etc. can causes kidney damage and ultimately electrolytes disturbances can be occurred. Ashwagandha (Withania somnifera) is an herbal plant may have some role on serum electrolytes balance. Objective: To observe the effects of ashwagandha (Withania somnifera) root on serum electrolytes against gentamicin induced nephrotoxicity in Wistar albino rats. Methods: This experimental study was carried out in the Department of Physiology, Sir Salimullah Medical College SSMC), Dhaka from 1st July 2010 to 30th June 2011. A total number of 35 Wistar albino rats, age from 90 to 120 days, weighing between 150 to 200 grams were selected for the study. After acclimatization for 14 days, they were divided into control group and experimental group. Control group was again subdivided into baseline control, (10 rats) and gentamicin treated control group, (10 rats). Again, experimental group (gentamicin treated group after ashwagandha treatment) consisted of 15 rats. All groups of animals received basal diet for 22 consecutive days. In addition to this, gentamicin treated control group also received gentamicin subcutaneously (100mg /kg body weight/day) for the last eight (15th to 22nd day) consecutive days. Again, gentamicin treated group after ashwagandha treatment received ashwagandha root extract (500mg/kg body weight/day, orally) for 22 consecutive days and gentamicin subcutaneously (100mg/kg body weight /day) for last eight (15th to 22nd day) days. All the animals were sacrificed on 23rd day. Then blood samples were collected and kidney weight was measured. For assessment of kidney function, some serum electrolyte levels e,g. serum sodium, potassium and chloride ion levels were estimated by ion selective electrode (ISE) electrolyte auto analyzer method, by using Biolyte 2000 auto analyzer. However, body weight and kidney weight of the animals were measured to assess the nephrotoxicity in these groups of animals. All these tests were done in the laboratory of Department of Physiology and Biochemistry, SSMC. Statistical analysis was done by one way ANOVA and Bonferroni tests as applicable. Results: The serum sodium and chloride ion levels were almost similar in all the groups and the differences were not statistically significant. The mean serum levels of potassium ion were significantly (p<0.001) lower in gentamicin treated group and (p<0.05) in gentamicin treated group after ashwagandha treatment in comparison to that of baseline control group. But this level of gentamicin treated group after ashwagandha treatment was significantly (p<0.01) higher than that of gentamicin treated group. Initial body weight was almost similar and no significant difference of this value was observed among the groups. Whereas, the final body weight was significantly (p<0.001) lower in gentamicin treated control group and in gentamicin treated group after ashwagandha treatment than that of baseline control group. Again this level of gentamicin treated group after ashwagandha treatment was significantly (p<0.05) higher in comparison to that of gentamicin treated control group. The kidney weight was significantly (p<0.01) higher in gentamicin treated control group when compared to that of baseline control and gentamicin treated group after ashwagandha treatment. Whereas, kidney weight of gentamicin treated group after ashwagandha treatment and of baseline control group was almost similar and showed no statistically significant difference of this value between this two groups. Conclusion: Ashwagandha (Withania somnifera) root extract may have some role in maintaining some of the serum electrolyte levels within normal limit, which indicates its nephroprotective effects against gentamicin induced toxicity. DOI: http://dx.doi.org/10.3329/jbsp.v7i1.11157 J Bangladesh Soc Physiol. 2012, June; 7(1): 29-35